Effect of Sn addition on age-hardening and precipitation behavior of Al-Mg-Si alloys with different Mg/Si ratios - TU Wenbin; TANG Jianguo; WANG Shanlin; MA Lehang; ZHAO Yan (Cailiao gongcheng, 2023)
The effect of Sn addition on age-hardening and precipitation behavior of Al-Mg-Si alloy with different Mg/Si ratios was investigated by using the hardness test and TEM characterization. The results indicate that the addition of Sn increases the number density of precipitates of the peak-aged alloy with low Mg/Si ratio, but decreases the precipitation rate of β″. Hence, the hardening rate and peak aging hardness of alloy with low Mg/Si ratio decrease by the addition of Sn. During over-aging, the high precipitate densities of Sn-added alloy improve the over aging hardness of the alloy with low Mg/Si ratio. For alloy with high Mg/Si ratio, the addition of Sn not only increases the precipitate density, but also enhances the precipitation rates of β″. Therefore, the hardening rate and peak-aging hardness of alloy with high Mg/Si ratio increase by the addition of Sn.